Strategi Strategi Konvergensi Media Harian Kendari Pos dalam Mempertahankan Eksistensi di Era Digital - Mahdar, Mahdar; Menungsa, Abdul Sarlan; Raihan, Muh. Akram (Al-MUNZIR, 2026)
Abstract The development of digital technology has brought major changes to the mass media industry, causing print media to face serious challenges in maintaining its existence. This study aims to analyze the media convergence strategy implemented by Kendari Pos Daily in maintaining its existence in the digital era. This study uses a descriptive qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observation, documentation, and literature review. The results show that Kendari Pos implements a media convergence strategy through technology integration, content diversification, and multiplatform distribution that includes print media, online news portals, and social media. This strategy enables Kendari Pos to expand its audience reach, increase interaction with readers, and maintain the relevance of its content or news amid digital disruption. This study concludes that Kendari Pos is implementing media convergence by combining journalistic practices across multiple platforms, namely print media, online media (website), and social media.